MrFbP: Markov random field‐driven spatial entropy‐based routing protocol in opportunistic networks. (26th October 2021) - Kumar, Arun; Dutta, Aniruddha A.; Jain, Nayan; Dhurandher, Sanjay K.
Summary: Recently, research towards technologies associated with the 5G communication is in full operation. Amongst these enabling technologies, device‐to‐device(D2D) communication is one of the critical factors for scaling up the network efficiency in 5G communication. Intermittent connections due to higher mobility lead to frequent path breaks, and hence a mobility‐based opportunistic routing is suitable enough to control the forwarding process. Opportunistic networks (OppNet) use the pairwise opportunistic contacts and higher mobility to rely on the store‐carry and forward mechanism for routing purpose. In this work, a novel mobility‐induced context‐based routing process has been designed to support D2D communication. The designed Markov random field‐induced protocol (MrFbP) is based on spatial entropy for capturing the coverage span of the forwarding node in the network. The work relies on the monitored historic mobility of a node and is then used to capture the utility metric for taking forwarding decision. MrFbP is compared against the established Direct Delivery (DD), Epidemic (EP), Spray & Wait (SW), and PropHet (PR) on parameters like throughput, delay, hops, overheads, and energy consumption. Simulation has been carried out using ONE simulator to validate an improvement in the design of a designed protocol against the baseline protocols. Abstract : The designed MrFbP is based on spatial entropy for capturing the coverage span of the forwarding node in the network. The work relies on the monitored historic mobility of a node and the MrFbP is compared against the established protocols on parameters like throughput, delay, hops, overheads, and energy consumption. Simulation has been carried out using ONE simulator to validate an improvement in the design of a designed protocol. The aggregated improvement over all the performance metrics of MrFbP is around 11%, 19%, 36%, and 56% over Spray & Wait, Prophet, Epedimic, and Direct Delivery, respectively.